(untitled) (Bangladesh Journal of Bioethics, 2013)
Animal research or animal testing is done worldwide, where vertebrate animals, from zebrafish to non-human primates, millions in number are used annually. The practice is regulated to various degrees in different countries. Scientists and science authorities still have their arguments to justify animal testing. However, dialogues and protests are also evident against it. Awareness and campaign in recent years has made scientists and governments make statement that animal testing should cause as little suffering to animals as possible and that animal tests should only be performed where necessary. We should also look into the matter deeply and compassionately. DOI: http://dx.doi.org/10.3329/bioethics.v4i3.17373 Bangladesh Journal of Bioethics 2013; 4(3):11-18